The making of modern poetry in Canada : essential commentary on Canadian poetry in English - Gnarowski, Michael, 1934-; Dudek, Louis, 1918-2001 (McGill-Queen's University Press, 2017)
"The Making of Modern Poetry in Canada gathers together primary literary documents including manifestos, reviews, critical essays, and recollections to illustrate the most significant developments in the rise modernist English Canadian poetry. Rather than present exclusively academic criticism, the editors have carefully selected original texts by the principal figures of modernism to offer readers a behind-the-scenes look at twentieth-century poetry in Canada. Collecting several decades of writings by luminaries beginning with pivotal essays by Sutherland and Smith, and including George Bowering, Northop Frye, Irving Layton, P.K. Page, F.R. Scott, Raymond Souster, and William Carlos Williams, this volume provides explanatory notes to guide the reader and to evaluate the significance of each in its literary and historical context. Each section begins with an overview of the contents and commentary on the significance of the presented literary evidence. This classic work of Canadian literary studies is now back in print with a substantial new introduction and appendices by Michael Gnarowski, who explains and interprets the essence of key initiatives in the unfolding of a modernist point of view. The Making of Modern Poetry in Canada offers a comprehensive chronological path from the earliest examples of Canadian modernism to the beginning of the postmodern period."--